EDUCATIONAL AIM OF TEACHING FOREIGN LANGUAGES (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
This article details why we learn and teach foreign language. The basic goal of learning a foreign language is to acquire the communicative competence, while the development and improvement of such competence is to some extent dependent of efficient and scientific teaching approach